Kemampuan Menulis Teks Cerita pada Mahasiswa Program Sarjana Pendidikan Bahasa Indonesia Fakultas Keguruan dan Ilmu Pendidikan Universitas Bengkulu - Didi Yulistio (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
The purpose of this study is to describe the ability to write story texts for students of the Indonesian Language Education Undergraduate Program FKIP Bengkulu University. The scope of this research covers aspects of (1) the suitability of the theme with the content, (2) the structure of the story text, (3) the choice of words (diction), (4) the use of story-style sentences, and (5) the Indonesian Language spelling and handwriting. This research uses descriptive method and quantitative approach. The research population was all students of the Indonesian Language Education Study Program FKIP Bengkulu University in the odd semester of 2018/2019 and the sample was purposive sampling, determining that there were 34 students in semester III-A. Collecting data uses test techniques and instruments in the form of instructions for writing stories with the theme of "love" and guidelines for assessing the ability to write stories based on five components, including content, text structure, diction, sentences, and mechanics. Data analysis used descriptive statistics to find the mean and determined qualitative results. The results showed that the ability to write story texts for the students of the Indonesian Language Education Undergraduate Program, FKIP Bengkulu University, was categorized as good. This is based on the score of all components with an average of 73.97. These results still require efforts to improve to be better. The results of each aspect of the ability to write story texts, namely aspects (1) the suitability of the theme with the content, good category (18.94), (2) story structure, good category (16.09), (3) accuracy of diction in good category (score 14 ,3), (4) narrative language style sentences are in good category (17.24), and (5) mechanics (BI spelling and handwriting) are in good category (7.32).